Covid-19 antibody discovery with topology-enhanced learning models - Wang, Zihong (Nanyang Technological University, 2022)
The recent global spread of Coronavirus disease 2019 (COVID-19) has been fueled by the appearance of various new variants of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), including Alpha, Beta, Gamma, Delta, Omicron, etc. The impact of variants on infectivity and monoclonal antibodies (mAbs) effectiveness is largely determined by how related receptor-binding domain (RBD) mutations affect ACE2 and antibody binding.